Relapsing polycondritis associated with microscopic polyangiitis: description of a clinical case - L. Breviglieri; F. Zizzi; P. Rocchi; G. Frascà; G. D'Arcangelo; C. Rimondi; L. Frizziero (PAGEPress Publications, 2001)
A clinical case of Relapsing Polychondritis (RP) with Microscopic Polyangiitis (MPA) is described in a 66 years old woman. This case rappresents a rare association of the two pathologies. Polychondritis is a rare infiammatory disease of unknown origin, but immunological mechanisms are essential in the pathogenesis. Histological features are infiammation and destruction of cartilage. The disease is systemic, may have a remitting course. The osteoarticular lesions are sometimes unusual, involving the temporomandibular or cervical articolations, and the renal lesions may be severe. This can be primary or associated with several other diseases. Microscopic Polyangiitis is a systemic disorder characterized by necrotizing vasculitis, affecting the small vessels. Most patient with MPA have Antineutrophil Cytoplasmic Antibodies for Myeloperoxidase (MPO-ANCA). ANCA have become an astablished tool for the diagnosis of systemic vasculitis. The primary target antigens for ANCA are myeloperoxidase (enzyme present in the secretory granules of neutrophils and monocytes) and antibodies to these antigens are tested by ELISA and IIF (indirect immunofluorescence). We describe a case of histologically confirmed MPA with Relapsing Polychondritis. Clinically she presented livedo reticulris in the lower limbs and pain in the joints. During the follow-up the patient developed asymetric oligoarticular arthritis. Immunosuppressive drugs like glucocorticoids and cyclofosfamide are the drugs of choice, depending on the stage and severity of the disease.